Deteksi Boraks pada Jajanan Sekolah melalui Edukasi dan Uji Alami Berbasis Kunyit - Indri Susanti; Zahrotus Saadah; Wafda Salami (Yayasan Inspirasi El Burhani, 2026)
Introduction: Food safety is crucial because it is related to nutritional intake. However, some foods, such as school snacks, contain dangerous food additives. One dangerous chemical that is still frequently misused in food is borax. This use of borax stems from producers' lack of understanding of the negative impacts of borax use and the lack of supervision of school snacks. This situation presents a problem for partners, particularly the community and consumers, who have limited knowledge and resources for detect the presence of hazardous chemicals in the daily food. This calls for an educational approach and simple testing methods that students, teachers, and parents can use to identify borax content in everyday foods. One inexpensive, simple, and natural-based testing method is the use of turmeric (Curcuma longa) as a natural indicator for qualitatively detecting borax. Objective: The purpose of this service was educate students about borax, its characteristics, and the impacts of its use. The activity also aims to test several samples of school snacks for the presence of borax using turmeric as a natural indicator. Method: This public service was conducted by education and simple experiments. The education included presentation of material about borax, its characteristics, and the impacts of its use. Meanwhile, simple experiments involved testing borax on several food samples using turmeric as a natural indicator. Result: The results of this community service activity showed an increase in participants' understanding of the educational material and the borax testing using turmeric as a natural indicator. This improvement was demonstrated by the average N-Gain value of 0.6957, which fell within the range of indicating a moderate increase in student understanding. The success of this activity was also demonstrated by the positive response from participants. Conclusion: This educational and experimental activity, as part of community service, was concluded to have run smoothly and successfully. This was demonstrated by the increased understanding of the educational material and the borax testing.